Challenges and Results at SDI Plus Imam Muslim in Character Building through Islamic Religious Education - Atsstaniya , Afida Alma; Eni Fariyatul Fahyuni (Indonesian Journal of Islamic Studies, 2024)
General Background: Character education is essential for fostering responsible decision-making and harmonious living among students in society. Specific Background: In Indonesia, the role of Islamic religious education (IRE) is critical in shaping the ethical and moral foundation of the nation’s youth, yet its implementation across various educational contexts remains inconsistent. Knowledge Gap: Despite the recognized importance of IRE, limited research addresses its impact on character development within specific educational institutions. Aims: This study investigates the character formation facilitated by Islamic religious education at SDI Plus Imam Muslim, examining both the positive outcomes and the challenges faced in this process. Results: Utilizing a qualitative approach, data collected through observations, interviews, and document analysis reveal that the IRE program at SDI Plus Imam Muslim has effectively integrated Islamic values into students' daily lives, leading to improved character traits such as respect and discipline. Novelty: This research highlights specific practices within IRE, such as communal prayer and daily rituals, that significantly contribute to character development. Implications: The findings underscore the need for ongoing evaluation and enhancement of IRE programs to overcome existing challenges and optimize character formation, suggesting that religious-based interventions can serve as effective tools for fostering moral and ethical behavior in students. Highlights: Islamic values enhance daily character formation in students. Continuous evaluation optimizes character education effectiveness. Qualitative research uncovers stakeholder perceptions and motivations. Keywords: Character education, Islamic education, student development, qualitative research, moral values.